Stock Market Mean Reversion and the Optimal Equity Allocation of a Long-Lived Investor - Campbell, John Y.; Cocco, João; Gomes, Francisco; Maenhout, Pascal J.; Viceira, Luis M. (Review of Finance, 2001)
Abstract This paper solves numerically the intertemporal consumption and portfolio choice problem of an infinitely-lived investor who faces a time-varying equity premium. The solutions we obtain are very similar to the approximate analytical solutions of Campbell and Viceira (1999), except at the upper extreme of the state space where both the numerical consumption and portfolio rules flatten out. We also consider a constrained version of the problem in which the investor faces borrowing and short-sales restrictions. These constraints bind when the equity premium moves away from its mean in either direction, and are particularly severe for risk-tolerant investors. The constraints have substantial effects on optimal consumption, but much more modest effects on optimal portfolio choice in the region of the state space where they are not binding. JEL classification: G12.